THE STRATEGY FORMULATION OF PHARMACY DEPARTMENT TO IMPROVE STAKEHOLDER SATISFACTION - Deviana Eka Oktaviantari; Lukman Hakim; Endang Yuniarti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Pharmacy department at Yukum Medical Centre Hospital (IFRS YMC) Central Lampung can not avoid the effects of tight business competition, so it needs to improve the services quality continuously. The purpose of this research was to analyse stakeholder satisfaction of pharmacy department services, and to formulate strategies to increase the stakeholder satisfaction. This research was a descriptive study with qualitative and quantitative data. Qualitative data were obtained by in-depth interviews, whereas quantitative data were acquired using questionnaires to measure satisfaction of stakeholder and pharmacy department staffs. The internal and external environments were analyzed, followed by SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The result was used as data to formulate strategies followed by Quantitative Strategic Planning Matrix (QSPM) test to sequence priorities of the chosen strategies as strategy development of IF RSYMC Central Lampung. The result stated that IFRS YMC Central Lampung had bigger opportunities (average score=1.36) than threats (1.27), and had smaller strengths (1.69) than weaknesses (1.73). The priority of alternative strategies based on QSPM test was developing technologies to support services, following national or international accreditation for hospitals, improving the capacity and quality of human resources in IFRS, and formulating a written standard operating prosedure to whole service in IFRS YMC Central Lampung.Keywords : SWOT analysis, QSPM test, Pharmacy Department,